Control of suddenly expanded flow for area ratio 3.61 - Syed, Syed Ashfaq; Khan, Sher Afghan; E., Rathakrishnan (rspublication, 2013)
Airflow from convergent axisymmetric nozzle expanded suddenly into circular duct of larger cross-sectional area than that of nozzle exit area were studied experimentally, focusing attention on the base pressure and the flow development in the duct. The flow parameters considered in this investigation are Mach number at the nozzle exit and the nozzle pressure ratio. The geometrical parameters considered are the area ratio between the sudden expansion duct cross-section and the nozzle exit area and the length to diameter ratio of the duct. To investigate the influence of active control on base pressure as well as on the flow field developed in the duct, the micro jets of 1 mm orifice diameter located at 900 interval along a pitch circle diameter (pcd) 1.3 times the nozzle exit diameter were employed as the controller of base pressure. The area ratio of the present study is 3.61. The nozzle pressure ratio (NPR) used were from 1.5 to 3, in steps of 0.5 and experiments were conducted for NPR 1.5, 2.0, 2.5 and 3.0. The length to diameter ratio of the enlarged duct was varied from 10 to 1, and tests were conducted for L/D 10, 8, 6, 5, 4, 3, 2 and 1. The experimental investigation on suddenly expanded flow field covering the above flow and geometrical parameters revealed that the base pressure is strongly influenced by the geometrical parameters viz length to diameter ratio, Mach number and the nozzle pressure ratio (NPR). The level of expansion at the nozzle exit (i.e. before sudden expansion) influences the base pressure very strongly.